REAL EARNING MANAGEMENT ANALYSIS ON COMPANY’S PERFORMANCE (CASE STUDY IN PANDEMIC TIME OF COVID-19) - Febryanti Simon; Clarissa Maya Devi; Yovita Ariani; Hansel Angga Winata (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The first case of Covid-19 was first stated in Indonesia on March 2, 2020. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) better known as the Corona virus is a new type of coronavirus that can be easily transmitted. Indonesia first imposed the large scale social restrictions called PSBB policy for the first time on April 15, 2020. PSBB is one of the government's efforts to break the chain of spread of Covid-19. There was a decrease of 70% of companies that conducted IPOs from before the Covid-19 period and during the Covid-19 period. The company's performance is the crucial matter in achieving the company's targets and for increasing returns for shareholders. The company's performance in this study was measured using Return On Assets (ROA). The ROA ratio is often used by management to measure the performance of a company and assess operational performance in utilizing the resources owned by the company. Real earning management is one of the ways that can be done by the management to achieve profit targets. In this study, it will focus on real earnings management. The selection of samples using purposive sampling and hypothesis tests is conducted using SPSS 25 with a signification rate of 0.05. The study shows abnormal CFO and discretionary expenses which are factors in measuring real profit management have a significant effect on the company's financial performance.